Associations of the Life’s Essential 8 with Parkinson’s disease: a population-based study - Chenguang Zhou; Oumei Cheng (Frontiers in Aging Neuroscience)
BackgroundParkinson’s disease (PD) is a progressive neurodegenerative disorder with increasing global prevalence. This study investigated the association between the American Heart Association’s Life’s Essential 8 (LE8) and PD prevalence using a large, nationally representative database.MethodsWe analyzed data from 18,277 participants aged 40 years and older from the National Health and Nutrition Examination Survey (NHANES) 2005–2018. LE8 scores were calculated based on diet, physical activity, nicotine exposure, sleep, body mass index, blood lipids, blood glucose, and blood pressure. PD cases were identified through self-reported anti-PD medication use. Multivariate logistic regression models were employed to examine the association between LE8 and PD prevalence, adjusting for various demographic and clinical factors. In addition, we performed restricted cubic splines (RCS), subgroup analyses, and weighted quantile sum (WQS) regression to verify the robustness of the study results.ResultsThe prevalence of PD was 1.3% in the study population. After full adjustment, individuals with moderate (50–79) and high (80–100) LE8 scores showed lower odds of PD compared to those with low (0–49) scores (OR 0.53, 95% CI 0.29–0.97 and OR 0.43, 95% CI 0.17–1.04, respectively; p for trend <0.05). A dose-response relationship was observed between LE8 scores and PD prevalence. WQS regression identified dietary factors and glycemic health as the main contributors to the inverse association between LE8 and PD.ConclusionOur findings suggest a significant inverse association between Life’s Essential 8 (LE8) and PD prevalence, with dietary factors and glycemic health emerging as the most influential components.